ANALYSIS OF THE IMPACT OF AGRICULTURAL POLICY ON MARKETING THE RICE CROP IN IRAQ FOR THE PERIOD (2000 - 2020) - Fatima K. Z; R. T. Al-Wasiti (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This research aims to study and analyze the impact of agricultural policy on marketing the rice crop in Iraq for the period 2000-2020 and to identify the actual contribution of agricultural policy and its positive role, regression analysis was used by OLS method to measure the impact of agricultural marketing policy in Iraq for the period 2000-2020, and it is necessary to increase the marketed quantities in a way that helps move the price According to the supply and demand of the marketed quantities, which increases the impact of the marketed quantities on the price while reducing the government support followed as an encouraging policy. The study concluded that the production was not sufficient to cover the local markets, which led the government to work on an encouraging policy by subsidizing rice prices due to the population increase to cover the domestic product from it and to meet the local need of the rice crop.